ANALYSIS OF COVERAGE OF POLITICAL THUGGERY BY SELECT MAINSTREAM NEWSPAPERS IN NIGERIA - Ogunbadejo, Samuel Idowu; Nweke, Chinyere Felicia; Chukwuemeka, Gloria Nwakego (African Journal of Social and Behavioural Sciences, 2024)
This study investigated how three major Nigerian newspapers covered political thuggery. The goal was to assess the frequency of political thuggery coverage in the newspapers and to identify the perspectives each paper presented between July and December. Content analysis was employed to gather data from news and feature stories on political thuggery in Nigeria during the period from July to December 2022. A total of 160 editions of the newspapers were analysed. The research was based on framing theory and conflict theory, using frequency tables and simple percentages to present the data. The study found that November and December 2022 saw the highest coverage of political thuggery in the newspapers. It also indicated that the predominant stance in the selected papers was that political thuggery should be deterred, with perpetrators arrested and prosecuted by the relevant authorities. The study suggested that there should be increased reporting on political thuggery in Nigeria and that journalists should receive training on how to cover and report on this issue to prevent escalation.